ADVANTAGES OF USING COMMUNICATION TECHNOLOGIES IN FOREIGN LANGUAGE TEACHING - Qodirova Gulbaxor Turdievna, Matkarimova Gulshanoy Axmadjonovna, Nuritdinova Yorqinoy Abdulxoshim qizi, Alimova Hurshida Tulkunovna (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
There has been a lot of discussion about the use of computers and the Internet in foreign language teaching for more than twenty years. Thus, information and communication technology (ICT) language teaching abroad has become the focus of researchers. Education, especially foreign language teaching, needs to be adapted and updated to adapt to the globalized world. The aim of this study is to explore the need for ICT and to highlight its positive impact in order to raise awareness of modernized communities in the modern digital world. To achieve this goal, the great advantages of the introduction of ICT in the process of teaching foreign languages will be demonstrated. By improving ICT, teachers and students will have the opportunity to communicate and collaborate with their native speakers and native speakers around the world. The use of ICT is also beneficial in them. When students write or speak for a wider and more international audience, they become more eager to learn and more active in the information age.